2018
DOI: 10.1002/jat.3659
|View full text |Cite
|
Sign up to set email alerts
|

Associations between household air pollution and reduced lung function in women and children in rural southern India

Abstract: Half of the world's population still relies on solid fuels to fulfill its energy needs for cooking and space heating, leading to high levels of household air pollution (HAP), adversely affecting human health and the environment. A cross-sectional cohort study was conducted to investigate any associations between: (1) HAP metrics (mass concentration of particulate matter of aerodynamic size less than 2.5 μm (PM ), lung-deposited surface area (LDSA) and carbon monoxide (CO)); (2) a range of household and socio-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 40 publications
(70 reference statements)
1
6
0
Order By: Relevance
“…Thus, the ndings only showed the impact of air pollution on adults and elderly population up to age 95. Secondly, the impact from global warming, indirectly caused by air pollution, on population health have been shown in several studies [14,16] ; however, the GBD estimations do not include those. Third, the level of PM concentration should be estimated from burning for any purpose, including cooking and heating, but the level of HAP data from GBD were quanti ed as the fraction of the population in each country that cooks with solid fuels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the ndings only showed the impact of air pollution on adults and elderly population up to age 95. Secondly, the impact from global warming, indirectly caused by air pollution, on population health have been shown in several studies [14,16] ; however, the GBD estimations do not include those. Third, the level of PM concentration should be estimated from burning for any purpose, including cooking and heating, but the level of HAP data from GBD were quanti ed as the fraction of the population in each country that cooks with solid fuels.…”
Section: Discussionmentioning
confidence: 99%
“…However, traditional indoor cooking and heating are still found in a considerable amount in low-and middle-income countries [11,12] . Low-income countries are likely to have higher use of solid fuels in houses than higherincome countries leading to health effects from HAP [13,14] , especially in African and Asian countries [15,16] .…”
Section: Introductionmentioning
confidence: 99%
“…De la Sota et al 33 measured LDSA in 3 households using traditional stoves in rural Senegal and reported a mean LDSA of 5085.9 ± 2980.1 µm 2 /cm 3 during cooking. Another study conducted in rural India found mean LDSA concentrations of 4677.5 ± 8550.7 µm 2 /cm 3 and 6648.6 ± 4845.3 µm 2 /cm 3 during cooking in kitchens with and without a chimney, respectively 43 . Our results add to this limited literature, which could serve as a reference for future studies.…”
Section: Discussionsupporting
confidence: 64%
“…Particulate matter (PM) is a key pollutant from health and environmental perspectives both indoors and outdoors. Exposure to PM is associated with various adverse health outcomes, such as cardiovascular disease, chronic obstructive pulmonary disease, and asthma. It is one of the leading global causes of mortality and ill health . A study quantifying the relationship between global mortality and ambient PM 2.5 estimated that ∼2 million premature deaths can be avoided by reducing PM 2.5 to 10 μg m –3 globally …”
Section: Introductionmentioning
confidence: 99%